Aspect controls on the spatial redistribution of snow water equivalence through the lateral flow of liquid water in a subalpine catchment - K. L. Mooney; K. L. Mooney; R. W. Webb (The Cryosphere)
Quantifying subalpine snowpack parameters as they vary through time with respect to aspect and position on slope is important for estimating the seasonal storage of snow water resources. Snow depth and density are dynamic parameters that change throughout the progression of the accumulation and melt periods, with direct implications on the distribution of snow water equivalence (SWE) across a landscape. Additionally, changes in density can infer physical processes occurring within the snowpack, such as compaction, liquid water ponding, and lateral flow. In this study, we measure snow depth and density throughout the Dry Lake watershed, a 0.25 km2 watershed in northern Colorado, USA, using L-band (1.0 GHz) ground-penetrating radar (GPR) and coincident depth probing. We calibrated these surveys using snow pit observations and a SNOTEL station. A physical snowpack model, SNOWPACK, with inputs from a local remote automated weather station and a SNOTEL station produced simulations of snow depth, snow density, and liquid water content (LWC). The model simulations indicate mid-winter melt events produced LWC on the south aspect that is less present in the north aspect and flat areas. These mid-winter melt events, in combination with observations, are interpreted to result in the lateral flow of LWC downslope and the redistribution of SWE. Further observations show a steady increase in soil moisture in sensors at the SNOTEL station throughout the winter in the flat terrain and ice layer formation on the south aspect snow pits during mid-winter surveys. Other key observations include ponding of liquid water at the base of the north aspect during the later spring season melt phase evidenced by GPR transects. We further develop a perceptual model for the aspect controls on the distribution and movement of SWE during the winter and spring seasons. In summary, for the Dry Lake watershed mid-winter melt events are observed on south aspects and interpreted to cause a redistribution of SWE downslope, while spring melt brings liquid water ponding at the base of north aspects. These differences in snowmelt dynamics are based primarily on aspect, providing important processes to consider for spatially and temporally extensive SWE measurements moving forward.